The Impact of Non-Financial Remittances on the Development of Developing Countries in Africa - Ojo, Sanya (Journal of Comparative International Management)

(untitled) (Management Futures, 2023)
This study explores and emphasises the utility of non-financial remittances to Africa’s developmental aspirations and the importance of critical thinking in the management of diaspora matters by agencies of government saddled with the diaspora affairs of developing countries in Africa. Drawing on the literature review and using the Socratic approach, the reflective analysis of this study demonstrates that greater value could be extracted from Africans’ diaspora remittances if more attention is focused on non-financial remittances and the remitters’ wellbeing. Through the exploration of the philosophical bases of the remittance processes, the study draws out non-financial remittances of ideas, skill, knowledge, technology, and innovation as a preferred and more valuable form of remittances with real effects on Africa’s economic growth and development. The study contributes by deepening our knowledge of non-financial remittances to the socio-economic development of less advanced countries, particularly in Africa.